2014
DOI: 10.3390/molecules191118493
|View full text |Cite
|
Sign up to set email alerts
|

Pterocarpan-Enriched Soy Leaf Extract Ameliorates Insulin Sensitivity and Pancreatic β-Cell Proliferation in Type 2 Diabetic Mice

Abstract: Abstract:In Korea, soy (Glycine max (L.) Merr.) leaves are eaten as a seasonal vegetable or pickled in soy sauce. Ethyl acetate extracts of soy leaves (EASL) are enriched in pterocarpans and have potent α-glucosidase inhibitory activity. This study investigated the molecular mechanisms underlying the anti-diabetic effect of EASL in C57BL/6J mice with high-fat diet (HFD)-induced type 2 diabetes. Mice were randomly divided into normal diet (ND), HFD (60 kcal% fat diet), EASL (HFD with 0.56% (wt/wt) EASL), and Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 50 publications
(54 reference statements)
1
37
0
1
Order By: Relevance
“…In this trial, the plasma TNF-α, IL-6 and PAI-1 levels were significantly decreased in the PT group after the 12 weeks of supplementation, although the interaction effect of time and group showed only the TNF-α level between the groups. In addition, a previous study showed that pterocarpan-enriched soy leaf supplementation led to inhibiting the gene expression of TNF-α and IL-6 in the white adipose tissue in type 2 diabetic mice [27]. Taken together, these observations indicate that the decreased TNF-α level may be induced by improving the plasma PAI-1 level.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In this trial, the plasma TNF-α, IL-6 and PAI-1 levels were significantly decreased in the PT group after the 12 weeks of supplementation, although the interaction effect of time and group showed only the TNF-α level between the groups. In addition, a previous study showed that pterocarpan-enriched soy leaf supplementation led to inhibiting the gene expression of TNF-α and IL-6 in the white adipose tissue in type 2 diabetic mice [27]. Taken together, these observations indicate that the decreased TNF-α level may be induced by improving the plasma PAI-1 level.…”
Section: Discussionmentioning
confidence: 69%
“…In a previous study, PT ameliorated the insulin sensitivity and β-cell dysfunction in type 2 diabetic mice [27]. However, no clinical trial has been conducted to examine the anti-metabolic disorder effects with the transcriptome analysis in PT-supplemented subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of soy leaves or their extracts has been implicated in preventing type 2 diabetes, obesity, heart disease and cancer through a multitude of mechanisms such as enhancing pancreatic β-Cell function and suppressing hepatic lipid accumulation [1], downregulating adipogeneic transcription [3], inhibiting α-glucosidase [4], decreasing non-HDL to HDL cholesterol ratio [5], relaxing carotid arteries [6], inhibiting fatty acid synthase [7], cancer cell specific cytotoxicity [8], and reducing DNA damage [9]. Much of the bioactivity of soy leaves is thought to be linked to isoflavonoids, kaempferol glycosides and pterocarpans [10], which are absent or found in extremely low levels in soy seed [10,11]. Kaempferols' antioxidative, free radical scavenging and anti-inflammatory properties [12,13] also play a synergistic role in the aforementioned health benefits.…”
Section: Introductionmentioning
confidence: 99%